Islamic Education and Gender Justice: A Study of Child Engagement in the Pakistani Diaspora - Haider, Syeda Dur e Nayab; Sadaf, Ayesha (Khalifa: Journal of Islamic Education, 2025)
There is a continuing practice of childhood engagements in which marriages are arranged at a young age, a long-standing tradition among many Pakistani families that serves to maintain kinship ties. This research paper examines the impact of migration and modernization on the practice of arranged marriages among Pakistani diaspora communities, particularly in relation to children’s access to education, including Islamic religious education. These families must balance traditional values with those of the host countries, which prioritize individual rights, gender equality, and legal obligations concerning education before marriage. A qualitative research design was applied using a multiple case study methodology. Data were collected through in-depth interviews with ten diaspora families, case studies in Pakistan, and secondary sources such as legal documents, sociological studies, and community reports. Data analysis was conducted thematically to explore how families adapted child engagement practices to host-country laws, social norms, and cultural expectations. The findings show that engagement still plays an important role as a marker of cultural continuity but has undergone significant transformation; i) marriages are postponed until legal and educational requirements, including religious education, are fulfilled; ii) there has been a shift toward a model in which individuals marry based on mutual consent; and iii) intergenerational conflicts arise when children prefer to continue their education rather than marry young. These results confirm that education, economic independence, and the value of equality in Islam are important factors in restructuring traditional practices. Thus, child engagement has not disappeared entirely but has been adapted into a more flexible pattern, allowing diaspora families to remain connected to their cultural heritage while ensuring children’s rights to Islamic education and personal autonomy in modern society.